ANALISIS TINGKAT KETAHANAN PANGAN RUMAH TANGGA PETANI PADI SAWAH TADAH HUJAN DI DESA PENGANDONAN DI KABUPATEN OGAN KOMERING ULU (JASEP, 2021)
Analysis of household food security level of rainfed lowland rice farmer in Penggendan Village District of Ogan Komering Ulu Regency is the largest food crop in Pengandonan sub district and majority of farmers in farming district are rice farmers. So that the rice crop in the village of production is the highest production. Rice-fed rice paddies are rice fields that only get water from rain water. Rainfed rice fields are usually in the rice field in the rainy season Ogan Komering Ulu District has a very large potential in agriculture in general food crops, especially that can be developed. The carrying capacity and and the land area of more than half the population work in the agricultural sector.Keywords: food security, rice, household